CYTOTOXICITY OF PUNARNAVA (BOERHAAVIA DIFFUSA L.) IN BREAST CELL LINE - Remya, *M J; Shahul Hameed, A; Sujathan, K (International Journal of Ayurveda and Pharma Research, 2018)
The incidence of cancer especially breast cancer is increasing alarmingly worldwide with a high percentage of death especially in developing countries. The Ayurvedic system treasures a host of medicinal formulations that have been shown to possess cytotoxic effects on tumor cell lines. Recently herbal medicines are coming to play a more vital role in the reduction and prevention of cancer. Boerhaavia diffusa L. (Punarnava), an annual herb has been used for managing wide range of diseases including cancer. This herb was also screened for various pharmacological activities like anti-inflammatory, anti-oxidant, immunomodulatory, anti-angiogenic, anti-metastatic activities and others. The decoction of root of Boerhaavia diffusa L. (Punarnava) was not scientifically evaluated for cytotoxicity. So the current study investigates the In vitro Cytotoxicity of root of decoction of Punarnava (Boerhaavia diffusa L.) in breast cell line (MCF-7). The five different concentrations of decoction of Punarnava (Boerhaavia diffusa Linn.) were used for In vitro Cytotoxicity by MTT assay at 24 hours and 48 hours. The test sample exhibits cytotoxicity of about 65.1±1.2at 800 µg/ ml concentration (48 hours) of incubation in MCF-7 breast cell line. The results were also analyzed statistically. It showed that there is highly significant difference in the percentage of inhibition of test sample in concentration from 50µg/ml -800µg/ml. The findings of this investigation concluded that the study drug Boerhaavia diffusa L. (Punarnava) has anti-cancer activity in MCF-7 breast cell line.